ANALYZING EMOTIONS THROUGH METAPHORS USED IN THE ALBUM DAWN FM (2022) BY THE WEEKND - Riyan Matin, - (Universitas Pendidikan Indonesia, 2023)
Metaphor area a useful tool to conveye ideas in a powerful way to persuade and convince people. This study aims to identify and specifically examine metaphors and emotions using the theory of George Lakoff and Mark Johnson (1980) for metaphors and Jonathan Culler (1997) for emotions. The data were obtained from the Dawn FM songs album by The Weeknd. In this study, which consisted of 4 songs. This study shows 5 metaphors and all of them contain sad emotions. In the second song, there are 2 metaphors that contain sad and happy emotions. The third song is found to be a metaphor and contains the emotion of anxiety, in the last song there is a metaphor and contains the emotion of sadness.